Studies on Inclusion Complexes of 2-(Benzothiazolyl-2')-hydrazono-3-phenyl-5-arylidene-4-thiazolidinone Derivatives with b-Cyclodextrin - Dash, S.; Sahu, R.; Garnaik, B.K. (Asian Journal of Chemistry, 2016)
A series of 2-(benzothiazolyl-2')-hydrazono-3-phenyl-5-arylidene-4-thiazolidinone derivatives have been synthesized starting from 2-hydrazinobenzothiazole.To enhance the solubility and bioaccessibility of these synthesized pharmacophores the inclusion complexes have been prepared with b-cyclodextrin. The synthesis of compounds and their inclusion complexes have been ascertained from their changes in physical, thermal and spectral characteristics (UV, IR and NMR). The stability constant and free energy change of the inclusion complexes have also been determined. The study suggests that inclusion complexes are appreciably stable and thermodynamically allowed. The synthesized compounds and their inclusion complexes have been screened for their possible antibacterial and antioxidant activities. The results revealed that compounds show better antibacterial and antioxidant activities after inclusion complex formation.